2020
DOI: 10.3389/fped.2020.575020
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Inequalities Increase the Probability of Ketoacidosis at Diagnosis of Type 1 Diabetes: A 2014–2016 Nationwide Study of 2,679 Italian Children

Abstract: This study aims to compare the frequency of Diabetic Ketoacidosis (DKA) at diagnosis in 2014-2016 with the one previously reported in 2004-2013; and to assess the association between family socioeconomic status and DKA at type 1 diabetes (T1D) diagnosis in children <15 years of age from 2014 to 2016. Methods: This nationwide, population-based, observational study included 2,679 children diagnosed with T1D from 54 Italian centers for pediatric diabetes during 2014-2016. The ISPAD criteria for DKA were used as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 26 publications
3
26
0
Order By: Relevance
“…In line with these studies, we observed that DKA was more common among the youngest children (<2 years of age), who also had the highest rates of severe DKA. The latter observation is in agreement with the published evidence, as DKA at diagnosis in younger children (especially <2 years of age) is usually more severe, and it is often a consequence of delayed treatment or diagnostic error ( 1 – 3 , 27 , 33 ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In line with these studies, we observed that DKA was more common among the youngest children (<2 years of age), who also had the highest rates of severe DKA. The latter observation is in agreement with the published evidence, as DKA at diagnosis in younger children (especially <2 years of age) is usually more severe, and it is often a consequence of delayed treatment or diagnostic error ( 1 – 3 , 27 , 33 ).…”
Section: Discussionsupporting
confidence: 91%
“…The main limitation of the present study was the lack of key demographic data, such as access to medical services and medical insurance, and in particular socioeconomic status, as numerous studies have reported that greater socioeconomic deprivation is associated with an increased risk of DKA at T1D diagnosis (9,11,27,32,(44)(45)(46)(47)(48)(49)(50)(51). Of note, a number of studies have shown an increased risk of DKA among ethnic minorities (11,23,45,50,52), and since ethnicity and socioeconomic status are strongly intertwined (53), our homogeneous cohort consisting solely of Han Chinese patients likely mitigated some of the potential effects of socioeconomic status.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…DKA can also develop in patients with well-known T1DM; it is referred to as recurrent DKA, and its frequency varies among different countries, reaching up to 8 per 100 person-years (15). Correct and timely diagnosis of T1DM and also careful follow-up of patients are the cornerstones for DKA prevention, which should be a goal for pediatricians (16,17). Several data records report an increased frequency of DKA during the COVID-19 pandemic (18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%